SOEP-IS 2014 - Determinants of attitudes to income redistribution - Christina M. Fong; Ilpo Kauppinen; Panu Poutvaara (Deutsches Institut für Wirtschaftsforschung (DIW), 2022)
SOEP has several questions that could be used to explain attitudes to income redistribution, but no measures of these attitudes. We propose including such questions. Together with existing SOEP questions, this would enable researchers to estimate the relative importance of self-interest, risk attitudes, fairness considerations, trust, personal economic experiences, and various other factors in explaining attitudes towards redistribution. We also suggest a pair of measures of beliefs about the causes of low and high income which have been shown to be important determinants of preferences for redistribution. Including these questions in the SOEP will afford researchers an unprecedented opportunity to investigate the effects of the factors listed above on the combination of beliefs about the causes of low and high income and attitudes to redistribution.
Keywords: 330